AIAA SPACE 2011 Conference &Amp; Exposition 2011
DOI: 10.2514/6.2011-7239
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Distributed Concurrent Engineering Teams: A Descriptive Framework for Aerospace Concurrent Engineering Design Teams

Abstract: As aerospace missions grow larger and more technically complex in the face of ever tighter budgets, it will become increasingly important to use concurrent engineering methods in the development of early conceptual designs because of their ability to facilitate rapid assessments and trades in a cost-efficient manner. To successfully accomplish these complex missions with limited funding, it is also essential to effectively leverage the strengths of individuals and teams across government, industry, academia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…20 Multidisciplinary optimization, the Design Structure Matrix, and the Task-Based Model are all approaches to engineering design that leverage the multidisciplinary nature by coordinating the knowledge flowing through the design process. [21][22][23][24] A review of research by Coates et al found that coordination is a concept that can be used to improve the engineering design process. 25 However, a wide range of models have been developed with little research to integrate these model's views into a cohesive and general perspective of coordination for engineering design.…”
Section: Design Knowledge Coordinationmentioning
confidence: 99%
“…20 Multidisciplinary optimization, the Design Structure Matrix, and the Task-Based Model are all approaches to engineering design that leverage the multidisciplinary nature by coordinating the knowledge flowing through the design process. [21][22][23][24] A review of research by Coates et al found that coordination is a concept that can be used to improve the engineering design process. 25 However, a wide range of models have been developed with little research to integrate these model's views into a cohesive and general perspective of coordination for engineering design.…”
Section: Design Knowledge Coordinationmentioning
confidence: 99%